Preliminary assessment of heavy metals in water and sediment of Karnaphuli River, Bangladesh - Ali, M.M.; Ali, M.L.; Islam, M.S.; Rahman, M.Z. (Elsevier, 2016)
Contamination of heavy metals in sediment is regarded as a global crisis with a large share in developing countries like Bangladesh. Four heavy metals such as arsenic (As), chromium (Cr), cadmium (Cd) and lead (Pb) in sediments and water were investigated from Karnaphuli River in Bangladesh. The decreasing trend of metals were observed in water as Cr > As > Pb > Cd and in sediment Cr > Pb > As > Cd. The ranges of heavy metals in water were 13.31-53.87, 46.09-112.43, 2.54-18.34 and 5.29-27.45 μg/L and in sediments were 11.56-35.48, 37.23-160.32, 0.63-3.56 and 21.98-73.42 mg/kg for As, Cr, Cd and Pb. The level of studied metals in water samples exceeded the safe limits of drinking water, indicated that water from this river is not safe for drinking and/or cooking. Contamination factor (CF) confirmed that the sediment samples were moderate to high contamination by As, Cd and Pb. The pollution load index (PLI) values were above one (>1) indicates advanced decline of the sediment quality. This study recommended that continuous monitoring of As, Cd and Pb in water; sediment and other aquatic biota of Karnaphuli River should be directed to assess the risk of these vital metals to safe the ecology in the vicinity of this river.